Gross motor dysfunction as a risk factor for aspiration pneumonia in children with cerebral palsy - Cut Nurul Hafifah; Darmawan Budi Setyanto; Sukman Tulus Putra; Irawan Mangunatmadja; Teny Tjitra Sari; Haryanti Fauziah Wulandari (Indonesian Pediatric Society, 2017)
Background Respiratory problems, such as aspiration pneumonia, are major causes of morbidity and mortality in children with cerebral palsy (CP) and greatly affect the quality of life of these children. Nevertheless, there is limited data on the incidence and risk factors of aspiration pneumonia in children with CP in Indonesia. Objective To determine the incidence and risk factors of aspiration pneumonia in children with cerebral palsy.Methods In children with CP aged 1-18 years, incidence of pneumonia was studied prospectively for 6 months and the prevalence of the risk factors was studied cross-sectionally. At baseline, we evaluated subjects’ by history-taking, physical examination, risk factors, and chest X-ray to assess the incidence of silent aspiration. Subjects were followed-up for six months to determine the incidence of overt or silent aspiration pneumonia.Results Eight out of 36 subjects had one or more episodes of aspiration, consisting of silent aspiration (2/36) and clinically diagnosed aspiration pneumonia (7/36). Subjects with more severe gross motor dysfunction experienced more episodes aspiration pneumonia, although it was not statistically significant (p = 0.06), while dysphagia (P=0.2) and nutritional status (P=0.11) were not associated with pneumonia or silent aspiration.Conclusion Twenty-five percent of children with CP experienced aspiration pneumonia during the 6-month study period, with gross motor dysfunction as a possible risk factor.